A Systematic Literature Review: Dampak Gamifikasi terhadap Motivasi Belajar Siswa Sekolah Menengah Pertama (SMP) - Mila Claudia Artika Sari; Fauziyah Az Zahra; Dinova Eka Putra; fransisca windiyanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Advances in digital technology in education have encouraged various learning innovations that enhance student engagement and motivation, including gamification. However, low motivation among junior high school students in conventional learning highlights the need for more interactive strategies aligned with the characteristics of the digital generation. This study aims to analyze the impact of gamification on students’ learning motivation, identify effective implementation forms, and examine factors influencing its success. The study employed a Systematic Literature Review method based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) workflow. Data were obtained from Google Scholar, ERIC, and SINTA databases, covering publications from 2021 to 2026. From approximately 200 identified articles, 10 key articles were selected through inclusion and exclusion criteria and analyzed in depth. The results show that gamification positively affects students’ learning motivation, as reflected in increased participation, enthusiasm, engagement, self-confidence, and enjoyable learning experiences. Its effectiveness is influenced by instructional design quality, challenge level, feedback systems, media usability, and educators’ readiness to integrate technology. Thus, gamification is a relevant innovative strategy for improving junior high school learning quality.